2021
DOI: 10.3390/life11060580
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy as a Possible New Approach in COVID-19: A Systematic Review

Abstract: COVID-19 is a viral disease characterized as a pandemic by the World Health Organization in March 2020. Since then, researchers from all over the world have been looking for ways to fight this disease. Many cases of complications arise from insufficient immune responses due to low immunity, with intense release of pro-inflammatory cytokines that can damage the structure of organs such as the lung. Thus, the hypothesis arises that photobiomodulation therapy (PBMT) with the use of a low-level laser (LLLT) may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…The multiple effects, proven by in vivo and in vitro studies, of PBM support the application of this therapeutic method both in the acute period of COVID-19 pneumopathy and in the sequelae period to reduce mortality and morbidity, increase the quality of life and socio-professional reintegration of patients. In fact, an analysis of the studies on PMB in COVID pneumopathy, which included 18 studies from the Pubmed/MEDLINE database, an article from the Web of Science; 3 articles from Google Scholar, which were selected according to rigorous criteria, concluded that PBM represents a promising approach in COVID-19 pneumonitis, having a demonstrated anti-inflammatory effect, which can especially counteract lung damage [25]. Pulsatile shortwave therapy uses the electrical component of the alternating highfrequency electromagnetic field (27.12 MHz).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple effects, proven by in vivo and in vitro studies, of PBM support the application of this therapeutic method both in the acute period of COVID-19 pneumopathy and in the sequelae period to reduce mortality and morbidity, increase the quality of life and socio-professional reintegration of patients. In fact, an analysis of the studies on PMB in COVID pneumopathy, which included 18 studies from the Pubmed/MEDLINE database, an article from the Web of Science; 3 articles from Google Scholar, which were selected according to rigorous criteria, concluded that PBM represents a promising approach in COVID-19 pneumonitis, having a demonstrated anti-inflammatory effect, which can especially counteract lung damage [25]. Pulsatile shortwave therapy uses the electrical component of the alternating highfrequency electromagnetic field (27.12 MHz).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the exact mechanism by which NIR increases iNOS is unknown, it is established that the resultant NO plays a key role in PBMT that could be utilized in COVID-19 treatment. Due to its ability to reduce platelet activation, and the role of platelet adhesion in thrombosis, NO has further potential to treat thrombosis in COVID-19 patients [95,96].…”
Section: Inos and Nomentioning
confidence: 99%
“…Another relevant approach is photobiomodulation therapy (PBMT), i.e., the light therapy based on non-ionizing types of light sources such as laser, that could be employed with or without application of a static magnetic field (sMF) [ 135 , 136 ]. Severe cases of COVID-19 arise when immune response in the patient’s body is insufficient and pro-inflammatory cytokines are extensively released and harm different organs such as lungs.…”
Section: Biomedical Applications Of Antiviral Nanomaterialsmentioning
confidence: 99%
“…Severe cases of COVID-19 arise when immune response in the patient’s body is insufficient and pro-inflammatory cytokines are extensively released and harm different organs such as lungs. As a supportive therapeutic strategy, PBMT utilizing a low-level laser (LLLT) raises immunity, stimulate tissue regeneration and decline pro-inflammatory cytokines [ 135 ]. De Marchi et al [ 137 ] studied the treatment of the patients suffering from severe COVID-19, who were in the need of mechanical ventilation, through PBMT-sMF.…”
Section: Biomedical Applications Of Antiviral Nanomaterialsmentioning
confidence: 99%